2013
DOI: 10.1371/journal.pgen.1004029
|View full text |Cite
|
Sign up to set email alerts
|

The PAF Complex and Prf1/Rtf1 Delineate Distinct Cdk9-Dependent Pathways Regulating Transcription Elongation in Fission Yeast

Abstract: Cyclin-dependent kinase 9 (Cdk9) promotes elongation by RNA polymerase II (RNAPII), mRNA processing, and co-transcriptional histone modification. Cdk9 phosphorylates multiple targets, including the conserved RNAPII elongation factor Spt5 and RNAPII itself, but how these different modifications mediate Cdk9 functions is not known. Here we describe two Cdk9-dependent pathways in the fission yeast Schizosaccharomyces pombe that involve distinct targets and elicit distinct biological outcomes. Phosphorylation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 66 publications
10
81
0
Order By: Relevance
“…In a recent paper, Wier and colleagues demonstrated that the interaction between the Rtf1 Plus3 domain and phospho-Spt5 is crucial for the recruitment of the PAF1C in S. cerevisiae (35). In S. pombe, however, Ctr9 is recruited independently of Rtf1 (30). Similarly, we found that human Paf1 was recruited to actively transcribed genes, apparently in an Rtf1-independent manner (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a recent paper, Wier and colleagues demonstrated that the interaction between the Rtf1 Plus3 domain and phospho-Spt5 is crucial for the recruitment of the PAF1C in S. cerevisiae (35). In S. pombe, however, Ctr9 is recruited independently of Rtf1 (30). Similarly, we found that human Paf1 was recruited to actively transcribed genes, apparently in an Rtf1-independent manner (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…In vivo, Mueller and Jaehning (2) showed that many of the phenotypes associated with paf1⌬ or ctr9⌬ are not enhanced but, rather, are suppressed by simultaneous deletion of RTF1 in S. cerevisiae. Another recent paper showed that Rtf1 and the PAF1C exert opposing effects on Pol II elongation in S. pombe (30). Figure 7 suggested that the PAF1C is recruited to some of its target genes independently of Rtf1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This seems to indicate that the Paf1 complex exerts a positive role on transcription. Of the three deletion strains tested (lacking Prf1/ Rtf1, Paf1, or Leo1-coding genes), the loss of Prf1/Rtf1 affects tolerance to H 2 O 2 to a lower extent than a lack of the other two components, consistent with a recent report indicating that this protein may not belong to the core of the Paf1 complex in S. pombe (25).…”
Section: Characterization Of a Reporter Of The Sty1-atf1supporting
confidence: 86%
“…[14][15][16][17] Interestingly, capping enzyme interactions with the Spt5 CTD are abolished by phosphorylation, whereas binding of the histone modification co-factor Rtf1 is enhanced. 13,21,24,25 As such, phosphorylation of the Spt5 CTD is beginning to emerge as an important part of the transition from early to late elongation.…”
Section: Landscape Of Histone Modifications Within Transcribed Genesmentioning
confidence: 99%